Strengthening Cost Structure and Revenue Stream Strategies Based on the Business Model Canvas in Dryland Farming Systems in Alor - Sulche Ifone Nafi; Jasintha Dessy Tapatfeto; Jonri Lomi Ga; Alexius Leonardo Johanis; Krista Arifinda Pailaka (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Dryland farming in archipelagic regions such as Alor Regency faces structural challenges, including limited water availability, high production costs, and low productivity. These conditions necessitate adaptive and technology-based business model innovations. This study aims to analyze strategies for strengthening the cost structure and revenue stream through a Business Model Canvas (BMC) approach supported by smart farming and renewable energy. The research was conducted using a community-based applied research method and a single-case study design involving the Batu Nirwala farmer group over four months. The analytical framework used included BMC analysis, before–after impact analysis, and qualitative thematic analysis. The results show that integrating solar power systems and automated precision fertigation can reduce energy costs to nearly zero, increase crop productivity, expand productive land by 80%, and promote income diversification through the development of derivative products and technology-based services. The implementation of these technologies also strengthens farmers’ institutional capacity and enhances the scalability of the business model in similar agroclimatic regions. This study contributes to the development of a technology-based sustainable agricultural business model framework in dryland areas and offers strategic implications for regional policy and agribusiness entrepreneurship development.